Influence of the entrepreneurial environment upon availability of real investments - Novotný, Josef; Myšková, Renáta; Jedlička, Vít (Univerzita Hradec Králové, 2019)
While evaluating investments, as a rule, first of all, investing criteria, which include yield, risk and liquidity, are being assessed. This step is usually performed by most of beginning and unprofessional investors. The goal of the paper is to draw attention the criterion which it is necessary to take into consideration while making decision about investment intentions as first, and – by this – to describe a method of its assessment. It comes from economic conditions, where each investor has a limited quantity of financial resources which is a limiting factor for him/her. The main problem is that a series of beginning investors is excited by whatever financial product and considers its future purchasing just to discover – after a certain period of time – that only part of solvent investors, who has a sufficient initial financial capital, is able to enter this field of investments. The benefit is that there are such investment products in the entrepreneurial environment the conditions of which can be adjusted so that they were maximally available for the general public. On the contrary, some other investments, however, precisely define a quantity and the minimal amounts which are to be at the investor’s disposal by the date of investment realization.
Vliv podnikatelského prostředí na dostupnost reálných investic
Keywords: Availability; real investment; entrepreneurial environment; Dostupnost; reálné investice; podnikatelské prostředí